Rudišče Knape - nekoč in danes - Križnar, Matija (Loški razgledi, 2009)
Mining has a long tradition in Slovenia and the area around Škofja Loka is no exception. There has been mining in Selca valley for many centuries. Mining was abandoned in the vicinity of Knape village about 1875, but the first written document about knape deposits dates back to 1533. Our investigation revealed that most of mining tunnels have been destroyed but we discovered some minerals in the mining bump, such as pyrite, sphalerite and galenite and some secondary minarals, such as gypsum and hidrozincite. The mine at Knape isimportant from the technical heritage and natural history aspect and it should be better documented and preserved.
Keywords: rudišča; mines; rudarstvo; geologija; geology; mineralogija; mineralogy; Knape; Škofja Loka; Selška dolina; Slovenia; Slovenija